METHOD OF CALCULATING GLOBAL BLOOD FLOW IN THE HUMAN BODY USING HETEROGENEOUS CALCULATION MODEL - Sharipov, Daler Kuchkarovich; Soliyeva, Dilfuza Tulkin kizi (INTERNATIONAL CONFERENCES, 2022)
In the articleas a basis for the global blood flow model (that is, a closed model describing the blood circulation in general) it is proposed to use a quasi-dimensional nonlinear model of the pulsating flow of a viscous incompressible fluid through an elastic tube.